2015
DOI: 10.1536/ihj.15-110
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Servo-Ventilation Has More Favorable Acute Effects on Hemodynamics Than Continuous Positive Airway Pressure in Patients With Heart Failure

Abstract: SummaryAdaptive servo-ventilation (ASV) has been attracting attention as a novel respiratory support therapy for heart failure (HF). However, the acute hemodynamic effects have not been compared between ASV and continuous positive airway pressure (CPAP) in HF patients.We studied 12 consecutive patients with stable chronic HF. Hemodynamic measurement was performed by right heart catheterization before and after CPAP 5 cmH 2 O, CPAP 10 cmH 2 O, and ASV for 15 minutes each.Heart rate, blood pressure, pulmonary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Simultaneously, the auto-EPAP modes developed by ASV-manufacturers are available in daily practice, but lack an evidence base for superiority on fixed-EPAP in clinical and bench studies [ 2 , 21 ], and consensual recommendations are clearly absent. The potential for cardiac output worsening due to specific pressure levels is not always counterbalanced by the neurovegetative response [ 19 , 20 , 22 ] and at-risk patients are likely those with a low pulmonary capillary wedge pressure [ 18 ] and a right ventricular dysfunction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, the auto-EPAP modes developed by ASV-manufacturers are available in daily practice, but lack an evidence base for superiority on fixed-EPAP in clinical and bench studies [ 2 , 21 ], and consensual recommendations are clearly absent. The potential for cardiac output worsening due to specific pressure levels is not always counterbalanced by the neurovegetative response [ 19 , 20 , 22 ] and at-risk patients are likely those with a low pulmonary capillary wedge pressure [ 18 ] and a right ventricular dysfunction [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…ASV therapy is exceedingly effective in a patient with higher PCWP. Asakawa et al demonstrated that ASV has more favorable acute effects on hemodynamics than continuous positive airway pressure (CPAP) in HF patients [21]. Furthermore, there have been several reports showing that ASV has better compliance than CPAP or bi-levelpositive airway pressure (BiPAP) [22].…”
Section: Discussionmentioning
confidence: 99%
“…PCWP was not mentioned in SERVE-HF but there might be a considerable number of patients with low PCWP. Asakawa et al reported an increase of stroke volume in CPAP 10 cmH 2 O was significantly higher than that in CPAP 5 cmH 2 O [21]. Furthermore, PEEP was also fixed 7.5 cmH 2 O in a randomized study of CPAP for patients with HF [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,13) Another group reported that predictors of increased SVI during ASV in HF patients included preserved right ventricular function, normal resting BP, non-ischemic HF etiology, mitral regurgitation, and increased left ventricular filling pressures. 14) Our finding that ASV treatment increased SV in HF patients with low TAPSE appears to contradict their report.…”
Section: Discussionmentioning
confidence: 99%